The practice of sport psychology: A youth coaches' perspective - Barker, S.; Winter, S. (International Journal of Sports Science and Coaching, 2014)
This research qualitatively documents youth sport coaches' perspectives of sport psychology and sport psychology consultants (SPCs) in the United Kingdom. Youth coaches are a unique population yet to be examined, despite their significance to the development of athletes. Semi-structured interviews were conducted with eight coaches who held a minimum of ten years experience with youth performers of a county to national level. Participants represented American football, hockey, soccer, and track and field. Inductive analysis identified twenty-four higher order themes, resulting in eight general dimensions: Role of sport psychology and SPCs, a sport psychologist's clientele, perceived work for sport psychologists, perception of where sport psychology belongs, expected characteristics of SPCs, professional accountability, and the facilitators and barriers of sport psychology. Results indicate youth coaches' support for the field of sport psychology, but the barriers SPCs face within youth sport are discussed. Consequently this article offers practitioners with applied solutions to overcome potential obstacles and improve current practices.